ASPEK HUKUM URF DALAM BERMUAMALAH - Sidik Ibrahim (State Institute of Islamic Studies (IAIN) Palu, 2006)
There is no doubt that the Qur'an and hadith are two main sources of Islamic law. They serve as guides for Muslims in both their individual and social lives. However, because of their dynamic lives, Muslims are in need of dynamic law. For this reason, urf (custom) serves as one of law studies that invites many Muslim scholars to give comments on whether or not urf can be considered a legal argument. It is within this context that this article will discuss urf and its legal argument to be implemented in Muslims’ social lives. Kata Kunci: Hukum Islam, urf, muamalah